Comparison of the Characteristics, Management, and Outcomes of STEMI Patients Presenting With vs. Those of Patients Presenting Without COVID-19 Infection: A Systematic Review and Meta-Analysis - Wang, Yanjiao; Kang, Linlin; Chien, Ching-Wen; Xu, Jiawen; You, Peng; Xing, Sizhong; Tung, Tao-Hsin (Frontiers in Cardiovascular Medicine, 2022)
Objectives: This study aimed to investigate the difference of the characteristics, management and clinical outcomes in patients with and without COVID-19 infection who suffered from ST-segment elevation myocardial infarction (STEMI). Methods: Data bases including Web of Science, PubMed, Cochrane Library and Embase were searched up to July 2021.Observational studies that reported on characteristics, management or clinical outcomes and published as a full-text article were included. Newcastle-Ottawa Scale (NOS) was used to assess the quality of all included studies. Results: A total of 27742 patients from 13 studies were included in this meta-analysis. Significant delay in symptom onset to first medical contact (SO-to FMC) time (mean difference= 23.42;95% CI:5.85 to 40.99; p =0.009) and door to balloon (D2B) time (mean difference= 12.27;95% CI:5.77 to 18.78; p =0.0002) was observed in COVID-19 patients. Compared with COVID-19 negative patients, COVID-19 positive patients had significantly higher level of C-reactive protein, D-dimer and thrombus grade (p<0.05), and showed more frequent use of thrombus aspiration and Gp2b3a inhibitor (p<0.05). COVID-19 positive patients also had an increase of in-hospital mortality (OR=5.98, 95% CI: 4.78 to 7.48, p<0.0001), cardiogenic shock (OR=2.75, 95% CI:2.02 to 3.76, p<0.0001) and stent thrombosis (OR=5.65, 95% CI: 2.41 to 13.23, p<0.0001). They also more likely to admit to intensive care unit (ICU) (OR=4.26, 95% CI: 2.51 to 7.22, p<0.0001) and had longer length of stay (mean difference=4.63;95% CI:2.56 to 6.69; p<0.0001). Conclusions: This study reveals COVID-19 infection had an impact on the time of treatment and shows a strong signal that STEMI patients presenting with COVID-19 infection are more thrombotic and had poorer outcomes.